2002
DOI: 10.2337/diacare.25.8.1308
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Disease and Carotid Artery Intima-Media Thickness in Japanese Type 2 Diabetic Patients

Abstract: OBJECTIVE -To investigate the association between carotid atherosclerosis, measured as intima-media thickness (IMT), and cardiovascular morbidity in type 2 diabetic patients. RESEARCH DESIGN AND METHODS -We investigated the relationship betweenIMT and coronary artery disease (CAD) in 40 type 2 diabetic patients and 40 control subjects. Diabetic patients with CAD determined by coronary angiography were consecutively recruited, whereas the control subjects were recruited from among diabetic outpatients without C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 23 publications
1
30
0
2
Order By: Relevance
“…Likewise, carotid IMT has consistently been shown to be greater in type 2 diabetic patients than in non-diabetic subjects [44][45][46]. In addition, IMT has correlated with the presence of CVD in type 2 diabetic patients [47].…”
Section: Discussionmentioning
confidence: 95%
“…Likewise, carotid IMT has consistently been shown to be greater in type 2 diabetic patients than in non-diabetic subjects [44][45][46]. In addition, IMT has correlated with the presence of CVD in type 2 diabetic patients [47].…”
Section: Discussionmentioning
confidence: 95%
“…The outcome measurement, CIMT is considered to be an appropriate measure for generalised atherosclerosis [32][33][34]. It is strongly related to several cardiovascular risk factors Values are expressed as linear regression coefficients, adjusted for gender and age, with 95% confidence interval in parentheses, and reflect changes in S.D.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the prevalence of CAD in middle-aged and older type 2 diabetic patients is approximately 0.1. It has been also reported that IMT was 1.27 0.07 mm (mean SD) in type 2 patients with CAD diagnosed by coronary angiography and 1.03 0.04 mm in patients without CAD, respectively 28) . Based on these previous findings, in this study, registration of 11 patients or more was required to detect a significant difference between subjects with and without CAD, if it is assumed that the standard deviation common to both groups is 0.07 mm, and -level and power are 5% and 90%, respectively.…”
Section: Sample Size and Statistical Analysesmentioning
confidence: 99%